Performance and sustainability of quaternary composite paste comprising limestone, calcined Hwangtoh clay, and granulated blast furnace slag. (November 2021) - Han, Yi; Lin, Runsheng; Wang, Xiao-Yong
Abstract: The cement industry has been increasing, and while meeting our construction needs, it has also brought environmental pollution. At present, reducing carbon emissions is an increasingly serious challenge facing the cement industry. The utilization of mineral admixtures (such as calcined clay, slag, and limestone powder) to replace partial cement is a direct way to lower CO2 emission. In this study, three supplementary cementitious materials (SCMs), i.e., limestone powder (0–10%), calcined Hwangtoh clay (0–20%), and granulated blast furnace slag (0–30%), were used to prepare binary, ternary, and quaternary mixtures. X-ray diffraction and attenuated total reflection Fourier transform infrared analysis were performed to characterize the mixed pastes. Furthermore, the workability, compressive strength, ultrasonic pulse velocity, surface resistivity, and heat of hydration of the mixed pastes were determined. In addition, we analyzed the sustainability of the quaternary mixed paste. The experimental results show that the calcined Hwangtoh clay can significantly reduce the workability of the cement paste. As SCM's content increases, the compressive strength, ultrasonic pulse velocity, cumulative heat of hydration, and carbon emissions of the mixed paste decreased while the surface resistivity increases. The compressive strength and ultrasonic pulse velocity have an apparent linear relationship (R 2 = 0.923). The quaternary mixed paste has the highest corrosion resistance and the lowest cumulative heat of hydration. Compared with pure cement paste, a paste containing a large amount of SCMs can reduce carbon emissions per unit strength. In summary, the quaternary mixed paste produced in this study is highly durable and sustainable and thus has wide application prospects. Highlights: Supplementary cementitious materials like LS, HT, and BFS are used to prepare multi-component pastes. Three groups of binary, ternary, and quaternary mixed pastes with different dosages are designed. The quaternary mixed paste exhibits the best durability performance. The quaternary mixed paste has superior sustainability.